2016 IEEE International Conference on Computational Photography (ICCP) 2016
DOI: 10.1109/iccphot.2016.7492875
|View full text |Cite
|
Sign up to set email alerts
|

High-speed imaging using CMOS image sensor with quasi pixel-wise exposure

Abstract: Several recent studies in compressive video sensing have realized scene capture beyond the fundamental trade-off limit between spatial resolution and temporal resolution using random space-time sampling. However, most of these studies showed results for higher frame rate video that were produced by simulation experiments or using an optically simulated random sampling camera, because there are currently no commercially available image sensors with random exposure or sampling capabilities. We fabricated a proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Increasing the compression ratio is also important because it can extend the observation time or depth range. Although a compression ratio of 8× was used in this study, a compression ratio of 32 has been demonstrated in [9,39] based on dictionary or learning-based methods. For specialized applications, such as TOF depth imaging, these methods can be efficient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the compression ratio is also important because it can extend the observation time or depth range. Although a compression ratio of 8× was used in this study, a compression ratio of 32 has been demonstrated in [9,39] based on dictionary or learning-based methods. For specialized applications, such as TOF depth imaging, these methods can be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Articles on compressive image sensors based on the image compression by analog or digital circuits are reviewed in [28]. The authors of [9,10] adopt a different signal compression scheme where the signal is compressed in the charge domain in pixel. This scheme is advantageous in temporal compression in terms of pixel size and power consumption.…”
Section: Compressive Sensing and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a coded exposure, a shutter function turns individual pixels "on" or "off" during the exposure, thus modulating light integration. Pixel-wise shutters can be realized electronically modifying the pixel architecture [34,53,32,50] or using spatial light modulators (SLMs) [20]. More specifically, we generate a TMCA by synchronizing a CA that changes its pattern in time -dubbed as a time-varying CA-and a spatially varying shutter-function realizing a coded exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of theoretical and experimental properties of compressive video cameras which utilize per-pixel coded exposure sequences has been done as well [5] - [7]. FPA implementations using programmable coded exposure sequences have also been developed [11], [12]. All of these algorithms work with an approach to maximize the information content in space and time using a compressed sensing approach which assumes the signal can be sparsely represented in a transform domain.…”
Section: Introductionmentioning
confidence: 99%